Trichosporon mucoides infection in an immunocompetent host. - García, Lucy; Osorio, Guiovana Fernanda (Colombia Medica, 2008)
A forty-year-old woman, hairdresser, presented a month history of progressive necrosis of the left fourth finger nailbed, accompanied by intense pain, without pathological antecedents and no trauma. Histologic examination showed extensive surface necrosis with abundant cell detritus and erythrocytes, within the necrotic tissue displacing the collagen. There were hyaline, birrefringent structures compatible with arthroconidia Tissue culture for aerobic as well as anaerobic bacteria and mycobacteria were negative. In tissue culture for fungus grew Trichosporon mucoides. A fluconazole therapy was initiated with 400 mg per week dosage, with clinical improvement. This fungus also normal soil inhabitant, is characterized by the presence of true hyphae, other members of the genus have pseudohyphae, arthroconidia y blastoconidia. T. mucoides can also be an opportunistic pathogen producing potentially fatal systemic infections in immunocompromised hosts. Cases of onychomycoses with this fungus as causative organism have been reported, but their symptomatology has not been as severe as in this case.